Candida Administration Worsens Cecal Ligation and Puncture-Induced Sepsis in Obese Mice Through Gut Dysbiosis Enhanced Systemic Inflammation, Impact of Pathogen-Associated Molecules From Gut Translocation and Saturated Fatty Acid - Panpetch, Wimonrat; Sawaswong, Vorthon; Chanchaem, Prangwalai; Ondee, Thunnicha; Dang, Cong Phi; Payungporn, Sunchai; Tumwasorn, Somying; Leelahavanichkul, Asada (Frontiers in Immunology, 2020)
Obesity induces gut leakage and elevates serum lipopolysaccharide (LPS), a major cell wall component of Gram-negative bacteria, through gut translocation. Since Candida albicans is prominent in human gut but not in mouse, C. albicans, a source of (13)-β-D-glucan (BG) in gut-contents, was administered in high fat diet (HFD)-induced obese mice at 1 wk prior to the sepsis induction by cecal ligation and puncture (CLP). As such, sepsis in Candida-administered obese mice was more severe than obese mice without Candida as determined by mortality, organ injury (liver and kidney), serum cytokines, gut leakage, endotoxemia, serum BG and fecal Gram-negative bacteria (microbiome analysis). In mice subjected to CLP and fed a HFD, but not treated with Candida demonstrated a similar mortality to non-obese mice with more severe gut leakage and higher serum cytokines. In vitro experiments demonstrated that LPS plus BG (LPS+BG) induced higher supernatant cytokines from hepatocytes (HepG2) and macrophages (RAW264.7), compared with the activation by each molecule alone, and were amplified by palmitic acid, a representative saturated fatty acid. The energy production capacity of HepG2 cells was also decreased by LPS+BG compared with LPS alone as evaluated by extracellular flux analysis. However, Lactobacillus rhamnosus L34 (L34) improved sepsis, regardless of Candida administration, through the attenuation of gut leakage and gut dysbiosis. In conclusion, an impact of gut Candida was demonstrated by Candida pretreatment in obese mice that worsened sepsis through i) gut dysbiosis induced gut leakage and ii) amplified systemic inflammation due to LPS, BG and saturated fatty acid.